CONCEPTUAL-STRATEGIC APPROACH TO STATE REGULATION OF MIGRATION PROCESSES - KRAVCHYK, YURII; POLISHCHUK, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
A new conceptual and strategic approach to state regulation of migration processes in Ukraine is substantiated. The content of the strategy in the practice of state regulation is determined with an emphasis on a certain sequence of actions. The provisions of the Strategy of the state migration policy of Ukraine for the period up to 2025 were analyzed. A retrospective analysis of the strategic regulation of migration in Ukraine was carried out, which confirmed the long process of uncertainty of conceptual principles. A new conceptual approach to the strategic regulation of migration in Ukraine is proposed, which provides for the consideration of the management object of migration as a process. It provides for the allocation of tasks at the stages of capacity building and preparation for migration, relocation, adaptation and integration, re-emigration, integration of migratory capital, assimilation, acculturation, naturalization. The doctrine of strategy development should be socio-economic growth as a defining management principle. The aim of the strategy is the state regulation of migration processes on the basis of security, order and regulation with the establishment of migration as an asset of socio-economic growth. The main provisions of the Strategy of state regulation of migration processes of Ukraine for the period up to 2027 with the distribution of goals and objectives in the following areas: ensuring the positive impact of migration processes on socio-economic development; ensuring sufficient dynamics of socio-economic development to curb migration losses; ensuring sufficient dynamics of socio-economic development through selective immigration. The goals of the Strategy are highlighted: basic - accounting and statistical, protective, institutional and legal, information and infrastructure; stage - with a list of tasks in terms of stages of the migration process.
Keywords: migration processes; state regulation; strategy; migration policy